2008
DOI: 10.1186/1749-7922-3-28
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and metabolic response to trauma in hypovolemic patients treated at a trauma center in Brazil

Abstract: Background: The metabolic changes in trauma patients with shock contribute directly to the survival of the patient. To understand these changes better, we made a rigorous analysis of the variations in the main examinations requested for seriously polytraumatized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Insulin resistance of peripheral tissues also occurs, reducing the utilization of the available glucose and enhancing the hyperglycaemia [86]. The current finding in goats is in line with Bahten et al [72] who reported that hyperglycaemia develops in most human patients of T/H. Experimental data from in vitro studies suggest that insulin and sex hormones interact.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Insulin resistance of peripheral tissues also occurs, reducing the utilization of the available glucose and enhancing the hyperglycaemia [86]. The current finding in goats is in line with Bahten et al [72] who reported that hyperglycaemia develops in most human patients of T/H. Experimental data from in vitro studies suggest that insulin and sex hormones interact.…”
Section: Discussionsupporting
confidence: 89%
“…In mice models , the ratio of lymphocytes decreased and both monocytes and neutrophils were not influenced by surgical trauma [64]. In contrast, in trauma-hypovolaemic human patients, the TLC, neutrophils and band neutrophil cells remained higher [72].…”
Section: Discussionmentioning
confidence: 95%
“…In order to establish a valid trauma model, one must demonstrate change in several parameters that re ect the degree of organ damage and shock. Those parameters include hemodynamics, blood biochemical pro le, endocrine pro le and in our model also markers of hepatic tissue damage (23)(24)(25)(26). Also histopathologic samples from liver tissues in a setting of shock demonstrate certain changes such as central lobular necrosis (27).…”
Section: Discussionmentioning
confidence: 97%
“…In order to establish a valid trauma model, we demonstrated changes in several vital components that reflect the degree of organ damage and shock. These include hemodynamic parameters, laboratory indices, such as blood and biochemical profile, endocrine profile, and markers of hepatic tissue damage [23][24][25][26] . Also, liver tissue samples in the setting of shock could demonstrate certain histopathological changes such as central lobular necrosis 27 , related to the level of injury.…”
Section: Discussionmentioning
confidence: 99%